Bollywood burglary - Stilton, Geronimo (Geronimo Stilton, 2016)
Asked by a Bollywood star for help protecting a valuable ruby, Geronimo Stilton and Hercule Poirat are inadvertently cast in the actress's film in spite of limited acting skills and are horrified when an anonymous thief makes off with the ruby.